Evaluation and comparison of a national made dental cartridge with two foreign made - Mahmood Hashemi H (Tehran University of Medical Sciences, 2006)
Background and Aim: Several factories produce dental cartridge in the world. In Iran, Daroupakhsh company is responsible for this task. The aim of this study was evaluate some properties of daroupakhsh cartridge and compare them with two imported ones: Ecocaine (made in Italy) and Septodont (made in France). Materials and Methods: In this experimental study, 70 healthy patients from maxillofacial clinic of Shariaty hospital were selected. After obtaining informed consent, 0.1 cc of each carpule was injected to the patients' frontal region and the extent of anesthesia was measured at different time intervals. Also the quality of injections was evaluated by 11 surgeons. The dimensions of the three cartridges were also measured and compared together. Data were analyzed by repeated measure ANOVA and Friedman with p<0.05 as the limit of significance. Results: There was no significant difference in extent and duration of anesthesia among the studied cartridges. Surgeons were equally satisfied of all three kinds of cartridges. All of the cartridges were aspirable. Conclusion: Based on the results of this study, the three studied cartridges had similar properties.